2014
DOI: 10.1002/jctb.4290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zeolite-coated anode on the performance of microbial fuel cells

Abstract: BACKGROUND: For a microbial fuel cell (MFC), the anode material plays a key part in power generation. Modification of conventional carbon-based anode materials is an effective strategy to improve MFC performance. RESULTS: Two different zeolites, namely, mobil catalytic materials number 41 (MCM-41) and NaX, were used to modify graphite felt anodes and compared with unmodified anodes in dual-chamber MFCs. Fourier transform infrared analysis verified that MCM-41 and NaX zeolites were successfully coated onto the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…It was reported that carbon cloth anode modified by nanoflaky nickel oxide delivered a maximum power density of 1024 mW m −2 , which was more than three‐fold higher than that of the plain anode . The recent proposed anode coated with zeolite could improve maximum power density and columbic efficiency value by 152.1 % and 36.2 % respectively , and there also have many interesting study in iproving the anode performance, including bioanode containing G. oxydans cells with ORP and K 3 Fe(CN) 6 , being firstly used in a MFC system . Besides, nanomaterials, polymers or electron redox mediators were anchored onto electrode surface to enable more conductive and electron transfer efficient anodes , .…”
Section: Introductionmentioning
confidence: 89%
“…It was reported that carbon cloth anode modified by nanoflaky nickel oxide delivered a maximum power density of 1024 mW m −2 , which was more than three‐fold higher than that of the plain anode . The recent proposed anode coated with zeolite could improve maximum power density and columbic efficiency value by 152.1 % and 36.2 % respectively , and there also have many interesting study in iproving the anode performance, including bioanode containing G. oxydans cells with ORP and K 3 Fe(CN) 6 , being firstly used in a MFC system . Besides, nanomaterials, polymers or electron redox mediators were anchored onto electrode surface to enable more conductive and electron transfer efficient anodes , .…”
Section: Introductionmentioning
confidence: 89%
“…stud-ied the performance of aN aX zeolite modified graphite felt anode in ad ual-chamber MFC. [33] After 20 days of operation, they found more bacteria on the modified anode than on the bare graphite felt anode. They reasoned that the bacteria accumulationw as caused by absorption of glucosem olecules on NaX zeolite.T he glucosea bsorption, as demonstrated by their control experiments,w as duet ot he hydrophilicity of NaX zeolite.…”
Section: Improving Biocompatibilitymentioning
confidence: 99%
“…Generally,a nodesw ith high surface roughnessfavor bacterial adsorption. [33] To gain sufficient space for bacteria, it would be rational to first select unmodified anodesw ith high effective surface. Since the initial use of graphite felt as the anode material, efforts have been devoted to increasing the surface area of carbon-based anodes.…”
Section: Providingmore Space For Bacteriamentioning
confidence: 99%
“…Then, the carbon felt (2 cm 2 ) was placed in the solution and sonicated for 30 min. The modified carbon felt was finally dried at 100 • C [12].…”
Section: Preparation Of Clay-modified Electrodesmentioning
confidence: 99%